Technical and Economic Efficiency of Devices for Ultrasonic Cleaning of City Bus Exhaust Gases - Pak, I.; Baurova, N.; Kurmasheva, B.; Karsakova, A.; Каdyrova, I. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2022)
The article substantiates the use of devices for ultrasonic cleaning of exhaust gases for city buses, provides the design and principle of operation of an accumulative device for ultrasonic cleaning of exhaust gases, as well as layout solutions for their placing on buses. A calculation method is presented that makes it possible to determine the main parameters of ultrasonic equipment for cleaning and disposal of exhaust gases from internal combustion engines of city buses, as well as to calculate the proportion of finely dispersed soot particles deposited, which characterizes the degree of purification of exhaust gases from fine soot particles, based on which there is calculated economic efficiency of ultrasonic cleaning devices.